Factors Affecting Work Efficiency’s Employee of Champalao Deposit Taking Micro Finance Institution: https://doi.org/10.69692/SUJMRD100448 - TAIKASEM, Anonh; Duangvilaykeo, Thipphavanh; KHOMTHAVONG, Phonepasit (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This Research aimed to study the motivation, efficiency in the operation of microfinance institution employees who receive deposits in Lao Pagoda and the factors that affect the performance of employees of microfinance institutions who receive deposits in Lao Pagoda. By using 50 sets of questionnaires to collect data from 50 target groups and the program SPSS software was used to analyze all the data. The research results found that the employee's work motivation is the motivation to monitor and evaluate the performance frequently with the value of = 4.47; SD=0.46, job responsibility is appropriate with value = 4.23; SD=0.57, types of work has a value of = 4.07; SD=0.58, Work improvement has value = 4.02; SD=0.72 and acceptance of each other within the organization staff has a value of = 4.01; SD=0.64. There is also a good relationship between colleagues with a value of = 4.22; SD=0.56, the level of productivity in the work function, value = 4.14; SD= 0.60, policy and organizational management has a value of = 4.01; SD= 0.65, working environment value = 3.96 ;SD= 0.71 and lastly labor cost and welfare value = 3.73; SD=0.73. The efficiency in the performance of the employee's work was in a high levels, such as good time management with a value of = 4.37; SD= 0.53, the quality of work performed = 4.31; SD= 0.48, in terms of the amount of work that can be done, the value of = 4.03; SD=0.54. Factors that affect the performance of microfinance institutions that accept deposits in Laos have only one factor such as job stability (X10) with a statistical significance level of 0.01.